Exploring the effects of vanillin and divanillin on murine osteosarcoma cells: evaluation of cellular response and proteomic analysis - Oliveira, Gabriela Silva Neubern de; Furlaneto, Camila Giatti; Tokuhara, Cintia Kazuko; Ventura, Talita Mendes Oliveira; Pessôa, Adriano de Souza; Fakhoury, Vanessa Svizzero; Pagnan, Ana Ligia; Inacio, Kelly Karina; Sanches, Mariana Liessa Rovis; Buzalaf, Marília Afonso Rabelo; Ximenes, Valdecir Farias [UNESP]; Oliveira, Rodrigo Cardoso de (Taylor & Francis, 2024)
The objective of this study was to evaluate the antitumor properties of vanillin and divanillin in murine bone tumour cells. The action of the compounds on the cell viability of the normal (MC3T3-E1) and the tumour cell line (UMR-106) was evaluated. Action of the compounds in colony formation, migration, and production of reactive oxygen species (ROS) in tumour cells were evaluated along with proteomic analysis. Both compounds affected the cell viability of normal and tumour cell lines, being divanillin the more effective. For UMR-106, both compounds reduced the cell viability by less than 50%. Vanillin inhibited the migration process, and divanillin decreased ROS production (p < 0.05). The proteomic analysis showed that both compounds acted in the expression of proteins involved in tumour progression. Our results suggest that vanillin and divanillin are effective drugs against murine bone tumour cells. They can be a promising alternative for the adjuvant treatment of bone cancer.
Keywords: divanillin; natural compounds; Osteosarcoma; vanillin